Évaluation de quelques activités biologiques des extraits aqueux et polysaccharidiques de dattes (Phoenix dactylifera L.) de la région de Ghardaïa - Abdelaziz, Aissa; Abismail Hedjoudja, Nacer (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab

Enquête Ethnobotanique des plantes médicinales utilisée pour le traitement des problèmes rénaux dans la wilaya de Ghardaïa - Baghbagha, Amel (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab; Médecine -- Mzab

Exploration des potentiels anti-radicaux des extraits de quelques espèces extrêmophiles au Sahara Algérien - Djekaoua, Meriem; Chenini, Ahlam (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab

Study of the antioxidant activity of some traditional date vinegar from the indigenous knowledge of the M’Zab valley populations (north-eastern Algerian Sahara) - Benhammadi, Zohra; Ould El Hadj, Mohammed Didi; Bouziane, Ghania; Eddoud, Amar; Kemassi, Abdellah; Chakou, Fatma Zohra; Khalifa, Sara; Benkhelifa, Nadjet (African Journal of Biological Sciences, 2025)
This study focuses on the physicochemical characterization and biological activities of some traditional date vinegars from the indigenous knowledge populations of the M’Zab valley (north-eastern Algerian Sahara). These are four types of vinegar made from different varieties of dates, including TemdjohoretTafezwine-Ghars (TTG), Ghars-Tafezwine-Azerza (GAT), H’Chef Deglet Noor (D1), and Ghars-Tafezwine-Azerza-Deglet Noor (ND). The analysis results show that the date vinegar samples studied are characterized by an acidic pH (3.15±0.02-3.62±0.00), high dry matter contents (3.98±0.17-8.47±0.06%), insoluble solids rate (8.1±0.06-15.05±0.03), in electrical conductivity (3.36±0.01-6.11±0.01ms/cm), and total acidity contents ranging from 14.17±2.40 for GAT to 39.8±0.92 g/l for TTG. The residual alcohol rates are 1±0.00% for the TTG sample to 4.9±0.00% for GAT. However, total sugar contents (0.88±0.1%7.36±0.57%) are more or less high in samples of traditional date vinegar, which gives a sweetness to some date vinegar samples. The protein contents (0.43±0.007-0.79±0.002) of the various date vinegar samples are low. Statistical analyses show that each type of traditional date vinegar has a distinct profile, influenced by the chemical characteristics of the cultivars used. The antioxidant activities of traditional date vinegar samples show their high antioxidant capacity for all types of radicals. Each sample of vinegar has significant antioxidant activities, although their activities are always lower than those of ascorbic acid (vitamin C) or Trolox. For each type of traditional date vinegar sample, it should be noted that the radical inhibition rates (FRAP, DPPH, and ABTS) are dosedependent. The sample with the highest antioxidant power remains GharsTafezwine-Azerza (GAT), with IC50 = 0.0538 mg product/ml distilled water for the DPPH test and IC50 = 0.0125 mg product/ml distilled water for the ABTS test. For a high reduction capacity by the FRAP test, it is 484.16±8.66 µM/ml equivalant Trolox.
Keywords: Botanique -- Mzab

Etude des activités biologiques d’une plante aromatique médicinale - Nasri, Kaoutar; Lebouabi, Zineb (Université de Ghardaia, 2024)
Keywords: Botanique -- Mzab; Eucalyptus globulus -- Mzab